2019
DOI: 10.1088/1755-1315/387/1/012075
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal effect on productivity of Bali cows in oil palm plantation in Riau Province, Indonesia

Abstract: This study was aimed to assess the effect of seasons on the productivity of Bali cows kept in oil palm plantation (OPP). The study used 20 Bali cows and 1 bull, which kept semi-intensively without supplementary feeding. Cow’s reproductive data, grouped according to birth time, dry season (DS) (May-October) and the rainy season (RS) (November-April) from August 2016 to September 2018, were used. These data were used to determine calving interval and calf mortality. Cows were weighed monthly to estimate dry matt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Based on these data, it can be concluded that the percentage of calf mortality is still at a very low limit. The mortality rate in calves can be influenced by genetic factors, seasons, nutritional aspects, quality of colostrum, quality of mother's milk, disease, maintenance systems, and management [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…Based on these data, it can be concluded that the percentage of calf mortality is still at a very low limit. The mortality rate in calves can be influenced by genetic factors, seasons, nutritional aspects, quality of colostrum, quality of mother's milk, disease, maintenance systems, and management [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study show that there is no difference in calf weight between both seasons (P > 0.05) (Table 1). The availability and quality of forage in the grazing area during the cow's pregnancy period is a determining factor in the quality of the calf (Maulana et al, 2019). Cows with good nutritional adequacy throughout pre-calving, which BCS shows, will positively impact the lives of those with better quality and health (calf immunity, morbidity, and mortality) (Mee, 2023).…”
Section: Calf Birth Weightmentioning
confidence: 99%
“…The cow's body weight begins to increase in the third to fifth month (weaning period) due to the cow's milk production decrease starting in the third month of lactation. Suppose you look at the research results on the calving interval of cows in the dry and rainy seasons, 381 and 428 days, respectively (Maulana et al, 2019). So.…”
Section: Adg Of Cows and Calvesmentioning
confidence: 99%
See 2 more Smart Citations